Therapeutic mechanisms of genistein in ischemic stroke: A systematic review of in vivo and in vitro studies - Mohd Khairudin, Nurin Yasmin; Mohd Azraai, Awla; Siran, Rosfaiizah; Azme, Nasibah (PLOS ONE, 2025)
Genistein is an isoflavone phytoestrogen that is considered a nutraceutical compound found in soybean. The mimicking of estrogen effects includes the ability to bind to the intracellular and cell membrane receptors of estrogen and exert biological functions like antitumor, anti-inflammatory, anti-oxidative, and antiproliferative properties. With more studies focusing on the therapeutic effect of genistein, both in vitro and in vivo, it is evident that genistein acts through multiple pathways including anti-apoptotic, anti-inflammatory, and anti-oxidative. As the effects of stroke are affecting more people and causing devastating repercussions, this warrants genistein to be utilized as a therapeutic drug. Therefore, further studies are due on the effects of genistein on humans so that clinical trials can be carried out for long-term benefits. This review encompasses various studies regarding the potential neuroprotective effects of genistein on cerebral stroke, examining both in vitro and in vivo experimental models. Four database searches: Web of Science (WoS), Scopus, PUBMED and Science Direct were searched from 1st January 1999 until 31st October 2025. The initial datasets identified through the database search yielded a total of 549 publications and 341 publications were finalized after removing duplicates. In the initial screening, a total of 293 studies were excluded due to their irrelevance to the main objective of this study. After assessing the suitability of the studies and following the PRISMA guidelines, a total of 31 articles were found to be suitable and systematically reviewed. Findings demonstrated the major mechanistic pathways involved in the therapeutic action of genistein are anti-apoptotic, anti-inflammatory, and anti-oxidative. Each of these mechanisms is governed by specific pathways, which will be thoroughly discussed, indicating that genistein can be effective as a therapeutic drug in ischemic stroke.